HOPANOIC ACIDS IN MESOZOIC SEDIMENTARY ROCKS - THEIR ORIGIN AND RELATIONSHIP WITH HOPANES - Farrimond P.; Griffiths T.; Evdokiadis E. (My University, 2002)
Hopanoic acids were found in all but the two most mature of a suite of 30 Triassic to Cretaceous sedimentary rocks. Their carbon number distributions generally maximise at C32, consistent with hopanoic acids found in modern sediments. The extent of isomerisation (measured by %ββ and %22S αβ parameters) is less for the acids than for associated hopanes, possibly due to increased isomerisation of hopanes in association with their generation from macromolecules and functionalised precursors. In immature samples the hopane carbon number distributions are consistent with an origin from defunctionalisation of hopanoic acids and other early diagenetically-formed hopanoids, whilst hopanes in more mature samples exhibit broader carbon number distributions indicative of side-chain cleavage during generation of macromolecularly-bound hopanoids.
Keywords: Mesozoic; Cretaceous; Triassic; Mesozoic; Мезозой::Триасовая; Мезозой::Меловая; Mesozoic::Cretaceous; Мезозой; Mesozoic::Triassic